Retinomotor response in the larvae of brown-marbled grouper, Epinephelus fuscoguttatus - Mukai, Yukinori; Leong, Seng Lim; Saad, Shahbudin (Academic Journals, 2012)
This study examined the retinomotor responses of 14 28, and 42 d old brown-marbled grouper Epinephelus fuscoguttatus under seven orders of magnitude of light intensities from 0 lx to 100 lx to determine the visual thresholds. The retinomotor response was absent in 14 d old larvae, indicating the absence of the rod visual cells and a reliance on pure-cone retina for vision. The 27–28 d old larvae had rod cells in the retinae and showed weak retinomotor response—the retinal pigment layer was slightly thinner at light intensity <1 lx than at 10–100 lx. The retinae of 42–45 d old grouper showed a clear retinomotor response at 0.1 lx, becoming stronger at 1 lx and higher; 0.1 - 1 lx may be considered the threshold of visual sensitivity of E. fuscoguttatus.